Characterization of FaDu-R, a radioresistant head and neck cancer cell line, and cancer stem cells. Issue 3 (June 2018) - Cho, Kwang-Jae; Park, Eun-Ji; Kim, Min-Sik; Joo, Young-Hoon
Abstract: Objectives: The aim of this study was to evaluate the impact of CSC on insensitivity to radiotherapy in HNSCC. Methods: A radioresistant cell line, FaDu-R, was established using fractionated ionizing radiation. Cells with high and low CD44/ALDH activity were isolated. Results: FaDu-R cells demonstrated significantly increased cell viability after radiation exposure compared with parental cells. CD44 high /ALDH high FaDu-R cells demonstrated significantly faster wound closure (p < 0.05) and more efficient invasion (p < 0.05) compared to the CD44 high /ALDH high FaDu cells or the CD44 low /ALDH low FaDu-R cells. There was a significant difference in tumor volume between the CD44 high /ALDH high FaDu-R cells and the CD44 high /ALDH high FaDu cells (p < 0.05) as well as the CD44 low /ALDH low FaDu-R cells (p < 0.05). Conclusion: Cancer stem cells (CSC) were associated with invasion and tumorigenesis in a radioresistant head and neck squamous cell carcinoma (HNSCC) cell line. This concept might help to improve the understanding of these mechanisms and to develop drugs that can overcome radioresistance during radiotherapy.